Madu Meningkatkan Kualitas Semen Kalkun Selama Penyimpanan (HONEY IMPROVE THE QUALITY OF SEMEN TURKEY DURING STORAGE) - Sari, Ni Made Dwi Permata; Bebas, Wayan; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2015)
This study aims were to determine the addition of various concentrations of honeyon themotility and viability of spermatozoa turkeywere diluted with phosphate yolk stored at 5°C for 72hours. This study used a completely randomized design factorial pattern. Four treatment groups,respectively: without the addition of honey (control), the addition of 3% honey, honey 4%, and 5% honey. A total of seven factors of each storage time: storage for 0 h, 12 h, 24 h, 36 h, 48 h, 60 h and72 h. Each treatment be repeated six times. Semen quality was observed in the form of examinationof progressive motility and viability of spermatozoa examination. The data obtained was examinedby the General Linear Model (Multivariate). The results showed that the addition of honey givessignificant differences on the progressive motility and viability of spermatozoa during storage. Itcan be concluded that the addition of 3% honey was the best dose to maintain motility and viabilityof spermatozoa turkeys during storage at 5°C temperature.
Keywords: honey; motility; viability; turkey’s semen